Electrochemical treatment of reverse osmosis concentrate on boron-doped electrodes in undivided and divided cell configurations - Bagastyo, A.; Batstone, D.; Kristiana, Ina; Escher, B.; Joll, Cynthia; Radjenovic, J. (Elsevier BV, 2014)
An undivided electrolytic cell may offer lower electrochlorination through reduction of chlo-rine/hypochlorite at the cathode. This study investigated the performance of electrooxidation of reverseosmosis concentrate using boron-doped diamond electrodes in membrane-divided and undivided cells.In both cell configurations, similar extents of chemical oxygen demand and dissolved organic car-bon removal were obtained. Continuous formation of chlorinated organic compounds was observedregardless of the membrane presence. However, halogenation of the organic matter did not result ina corresponding increase in toxicity (Vibrio fischeri bioassay performed on extracted samples), withtoxicity decreasing slightly until 10 Ah L-1, and generally remaining near the initial baseline-toxicityequivalent concentration (TEQ) of the raw concentrate (i.e., ~2 mg L-1). The exception was a high rangetoxicity measure in the undivided cell (i.e., TEQ = 11 mg L-1at 2.4 Ah L-1), which rapidly decreased to4 mg L-1. The discrepancy between the halogenated organic matter and toxicity patterns may be a con-sequence of volatile and/or polar halogenated by-products formed in oxidation by OH•electrogenerated at the anode. The undivided cell exhibited lower energy compared to the divided cell, 0.25 kWh gCOD-1and 0.34 kWh gCOD-1, respectively, yet it did not demonstrate any improvement regarding by-productsformation.